Interdisciplinary Management of Maxillary Canine Buccal Ectopia Associated with Peg Shaped Lateral Incisor - Karuna Singh Sawhny; Asheesh Sawhny (Case Reports in Dentistry)
Aligning a displaced maxillary canine into the dental arch is one of the most complicated problems in orthodontics. In cases of extremely high displacement, the tooth is frequently removed surgically. Because of the upper canines’ significance to dental esthetics and functional occlusion, such a decision is a very serious one. The purpose of this report is to illustrate an interdisciplinary approach involving both orthodontic management and conservative tooth restoration. The case was treated through an orthodontic nonextraction fixed appliance mechanotherapy for successful alignment of buccally ectopic upper left canine followed by a conservative direct composite tooth buildup of peg lateral incisor associated with the upper left ectopic canine in a 16-year-old adolescent North Indian female. Posttreatment records demonstrated good alignment of the displaced tooth and restoration of normal anatomy of the peg shaped lateral incisor.